SYSTEMATIC REVIEW OF THERAPEUTIC POTENTIAL OF AEGLE MARMELOS (LINN) IN THE MANAGEMENT OF ULCERS: EFFICACY, MECHANISMS AND CLINICAL APPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
Many people suffer from ulcers, a common gastrointestinal ailment characterized by the erosion of the stomach and duodenal lining. These ulcers are classified into two categories: duodenal and stomach ulcers, collectively referred to as stomach ulcers. Synthetic medicines can treat ulcers, but they are more expensive and may have more side effects compared to herbal remedies. Recent research has linked Helicobacter pylori infection of the gastrointestinal tract lining to stomach ulcers. Various herbs and herbal preparations have been found effective in protecting against or treating peptic and gastric ulcers. In ancient India, the plant Aegle marmelos, also known as Bael, was revered in mythology and traditional medical systems like Ayurveda. Every part of the tree, including the root, bark, fruit, leaf, and flower, is valued for its therapeutic properties in treating various conditions. Native to India, Aegle marmelos belongs to the monotypic genus Aegle of the Rutaceae family and is renowned for its numerous nutraceutical and therapeutic qualities